PERBEDAAN KEPADATAN TELUR AEDES SPESIES PADA AVITROP YAI\G DIPASANG DI DALAM RUMAH DAN DI LUAR RUMAH DI DESA KANDANGREJO, KLAMBU, GROBOGAN TAHUN 2OO4 - Margo Utomo; Sigit Tyasmono; Sayono - (Jurnal Kesehatan Masyarakat Indonesia, 2005)
Background: Dengue fever was the deadly disease, neither hqs cure nor vaccine. The only way to effectively and efficiently prevent the disease is by cleaning up the mosquitoes' hideouts. Ovitrap is a way to get ricl of the disease vector by reducing the number ofmosquitoes through their eggs. Purpose: to describe and analyze the density ofthe Aedes Species' eggs in the ovitraps installed in Kandangrejo, Subdistrict Klambu, regency of Grobogan. Method; This research is explanatory research with experiment method by the Post Test Only With Control Group Design. Researchsubiect is the eggs trapped in the ovitraps placed both inside snd outside the house. The sample is determined by Systematic Random Sampling. The variables covered in the research are; ovitrap inside and outside the house and the number of aedes species' eggs and its density, and measured with ovitrap index. Result: Kandangrejo, Subdistrict Klambu, the regency of Grobogan is an endemic area for Dengue with Container Index (CI); House Index (HI) dan Breuteau Index (BI) startfrom the month of January until May 2004 between 13,3 - 30,7 % ; 19,4 - 41,8 % and 2j,2- 64,4 %. The Ovitrap Index inside the house is 12,50 ok whereas the ovitrap index outside the house is 30,00 %.Conclusion:There is no dffirence between the eggs' density of the Aedes Sp in the ovitrap placed inside the house with the ovitrap placed outside the house (p : 0,653). After being identified, the eggs captured in the ovitrap inside the house are Ae. aegepty, whereas those captured outside the house is Ae. Albopictus .Keywords: Eggs density, ovitrap, Dengue Fever.